Analyses hi· et tridimensionnelle de problemes de contact avec frottement par une methode mixte des elements finis - Feng, Zhi-Qiang; Touzot, Gilbert (European Journal of Computational Mechanics, 1992)
This paper is devoted to the analysis of the two and three dimensional frictional contact problems between deformable bodies. A mixed finite element method is developped. The method uses the condensed flexibility matrix obtained by eliminating all the nodes except those where contact likely occurs. An incremental iterative procedure is used to solve this problem. Numerical examples are carried out in three cases : 2D rigid-deformable, 2D deformable-deformable and 3D deformable-deformable. The influence of friction effects on the local stress and contact pressure along the contact surface is shown. The numerical results prove that this approach is in very good agreement with known solutions and the number of iterations and the CPU time required are very small, compared to other available methods.